Appropriate antivenom doses for six types of envenomations caused by snakes in taiwan - C Chieh-Fan (Journal of Venomous Animals and Toxins including Tropical Diseases, 2009)
Six of the 15 species of venomous snakes found in Taiwan are responsible for most of the clinically significant envenomations in the country. These species are: Trimeresurus mucrosquamatus, Trimeresurus stejnegeri, Naja atra, Bungarus multicinctus, Deinagkistrodon acutus and Daboia russelii siamensis, which together can be subdivided into three groups based on their venom effects. Primary treatment consists of rapid administration of appropriate antivenoms. The present study aimed to identify a proper dose of antivenom for each snake group as well as to describe hemorrhagic, neurotoxic, and mixed effects of their venoms. A retrospective chart review identified 72 snakebite cases referred to an emergency department. Data on epidemiology, examination findings, snake identification, treatment, antivenom dose and complications were collected. After excluding 14 patients, data from 58 victims were analyzed. Most studied cases were male (86%). Significantly higher doses of antivenom were administered against neurotoxic envenomations (mean dose: three vials) compared with the other two (p < 0.05). Moreover, patients affected by neurotoxic bites were more likely to develop blurred vision and other complications (p < 0.05). Multivariate logistic regression analysis indicated that neurotoxic envenomation was a risk factor for complications (OR: 8.84, 95% CI: 1.06-73.73). Neurotoxic envenomations and complication occurrence were positively correlated with antivenom dosage. In conclusion, patients affected by neurotoxic envenomations received higher doses of antivenom than others whereas incidence of complications was associated with higher antivenom doses.